Cognicise – a new model of exercise - Gronek, Piotr; Adamczyk, Jan; Celka, Roman; Gronek, Joanna (Akademia Wychowania Fizycznego w Poznaniu)
Many physical activity centers for geriatrics and gerontology all over the word are examining the best fitted type of exercise for older people including endurance, resistance, stretching and cognitive intervention. Pro-health training is a special area of activity on the border of health prophylaxis, rehabilitation and even sports. The modern neuroscience provides a lot of evidence that in the older people exercises enhance plasticity of the brain networks. The aim of this review is to explicate the topic of cognicise training for older people that is combining of cognitive and exercise tasks.
Keywords: cognicise; older adults; exercise; healthy aging